Rancangbangun Starter Elektrik Portabel untuk Mesin Traktor Tangan - Geraldo Adinugra Rimartin; Bambang Purwantana; Radi Radi (agriTECH, 2020)
Indonesian farmers used to utilize crank to turn on hand tractor machine till today. It may make operators weariness and potentially raised work accident. The purpose of this study was to design a portable electric starter for hand tractor machine. Moreover, the study was addressed to evaluate the performance of the design. The minimum rotational speed (n) and initial torque (T) in decompression and non decompression conditions were adopted to calculate the minimum power (P) requirement. The minumum power of decompression and non decompression were 572.78 watts (≈ 0.74 hp) and 841.75 watts (≈ 1.09 hp), respectively. These values used as a reference in determining the main components, namely the wet type 12 volt battery and the serial type direct current starter motor. The next step, set up additional components, transmission mechanism, as well as concept of portable electric starter. The design was realized by construction and assembly process. A performance test was carried out on the prototype. The performance test of non decompression showed 1.88 seconds for working time, 264.56 Joules for workload (operator), 363.20 rpm for rotating speed and 0.68 watt hours for power requirement. Overall, application portable electric starter indicated better performance than crank. This study proved a high preference of operator on application of portable electric starter in decompression conditions.